Determinant Factors Influencing the Interest in Halal Certification: The Perspective of MSMEs in Indonesia - Agustiningsih, Maulida Dwi; Savitrah, Ravika Mutiara; Islami, Novita Nurul; Lestari, Putri Catur Ayu (Department of Islamic Economics, IPB University, 2024)
The halal industry is overgrowing, including in Indonesia, with the largest Muslim population in the world. Indonesia is ranked 19th as a producer and ranked 3rd as a consumer in the global halal industry. Although one of the halal certifications for MSMEs is free, only 1% of MSMEs in Indonesia are already halal certified. This study aims to analyze empirically the factors that influence the intensity of MSMEs in Indonesia to register for halal certification. A quantitative approach is used in this research by distributing questionnaires using the Likert scale to MSMEs. A total of 122 valid data collected were analyzed by adopting SEM-PLS. The analysis found that external factors had a dominant influence on the intention of MSMEs to register their products in halal certification, consumer pressure with a t-statistic of 4.328, and government policies with a t-statistic of 2.976. Moreover, one of the internal factors, awareness, is accepted with a t-statistic of 2.065. Meanwhile, benefits, competitors, and religiosity are not proven to affect halal certification. The data will help plan interventions from the government to encourage MSMEs to register their products in halal certification. The government should focus on assisting halal certification for MSMEs intensively.